PENGARUH PEMAHAMAN TENTANG PERPAJAKAN, KUALITAS PELAYANAN FISKUS, SISTEM TRANSPARANSI PERPAJAKAN, KESADARAN WAJIB PAJAK, DAN SANKSI PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI - Aglista Ramadhanty; Zulaikha Zulaikha (Diponegoro Journal of Accounting, 2020)
Each year, the number of individual taxpayers increase, but it is not accompanied by their compliance. This study aims to examine the influence of tax payer knowledge, fiscus service quality, tax transparency system, tax payer awareness, and tax penalties on the individual taxpayer compliance. The samples using convenience sampling technique were 400. Data were collected by Google Form survey that were distributed by Whats App group. Data and hypothesis were analized  using multivariate analysis of SPSS 21.  The results indicate that the taxpayer knowledge, fiscus service quality, tax payer awareness, and tax penalties have a positive significant effect on taxpayer compliance. Whereas the tax transparency system have no significant effect.